Model Hands on Mathematics (HoM) Berbantuan LKPD Bernuansa Islami Materi Garis dan Sudut - Dewi, Wiwik Sulistiana; Supriadi, Nanang; Putra, Fredi Ganda (Desimal: Jurnal Matematika, 2018)
This study aims to find out whether there is the influence of learning model of Hands-On Mathematics with the help of learner worksheet (LKPD) integrated on Islamic values to critical mathematical thinking ability on the subject line and angle. The research method used is experimental research. The type of research is Quasi-Experimental Design research. The instruments used are critical thinking skills tests online and angle learning materials. Data analysis using one-way ANOVA test with the same cell. The conclusion of this research is that there is the influence of learning model of Hands-On Mathematics with LKPD which is integrated on Islamic values to students' mathematical critical thinking ability better than another learning model.